2005
DOI: 10.3151/jact.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Coupled Corrosive Product Formation, Migration into Crack and Propagation in Reinforced Concrete Sections

Abstract: This paper aims to numerically simulate corrosion induced cracking, its propagation over sections of reinforced concrete members and the penetration of corrosive gel product into crack gaps. A coupled steel core and surrounding corrosion product are mechanically represented by a fictitious growing composite, with which the corrosive cracking initiation and subsequent propagation are simulated by 2D nonlinear crack analysis. The injection of corrosive gels into evolving cracks is substantiated in cases where co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…To simulate the corrosion-caused cracking in RC structures, a two-phase mechanical system [22,24], which is composed of corrosion products with non-corroded steel as one integrated phase (or a composite) and concrete as another phase, is employed. With the increase in corrosion product, the corrosion products and noncorroded steel are combined together to form a steel-corrosion product composite, which can be regarded as a cylinder subjected to a restraining pressure P rust,i .…”
Section: Deformation Compatibility and Force Equilibrium In The Radiamentioning
confidence: 99%
“…To simulate the corrosion-caused cracking in RC structures, a two-phase mechanical system [22,24], which is composed of corrosion products with non-corroded steel as one integrated phase (or a composite) and concrete as another phase, is employed. With the increase in corrosion product, the corrosion products and noncorroded steel are combined together to form a steel-corrosion product composite, which can be regarded as a cylinder subjected to a restraining pressure P rust,i .…”
Section: Deformation Compatibility and Force Equilibrium In The Radiamentioning
confidence: 99%
“…However, most of the analytical results reported so far were obtained using individually developed finite element package, and were validated using galvanostatic experimental results, which actually differ from those in real world of corrosion damaged concrete structure [21]. In particular, little attention has been paid to the engineering interpretation of FE results and the effect of key parameters of a concrete beam on its cracking and delamination.…”
Section: Introductionmentioning
confidence: 99%
“…According to FE results, it has been found that the cracking of concrete initiates and develops as a result of an increase of the radial expansion of corroding bars. If the permeation of corrosion products from a corroding bar into its surrounding concrete cover and into the developed cracks were taken into account, both critical amount of corrosion for concrete cracking and the width of concrete cracks could be well estimated [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a realistic and quantitative description, as well as a reliable prediction of the damage process due to corrosion of the reinforcement, is not possible yet. A major deficiency in previous investigations is the ignorance of a constitutive model for rust [3,4]. Thus, it is impossible to evaluate realistic time intervals for the appearance of corrosion damage.…”
Section: Introductionmentioning
confidence: 99%